(untitled) (Contemporary Journal of Social Science Review, 2025)
The enactment of the 26th Constitutional Amendment in Pakistan marked a significant reform, aiming to restructure the judicial appointment process for superior courts by altering the composition of the Parliamentary Committee. This research provides a critical and comparative analysis of this amended framework, contrasting it with the long-established systems for appointing High Court and lower court judges in the United Kingdom and the United States. The study argues that while each system represents a distinct approach to balancing judicial independence with accountability, the Pakistani model post-26th Amendment remains a unique hybrid, grappling with inherent tensions between judicial, executive, and parliamentary influence. Through a qualitative comparative legal analysis, this article examines the constitutional and statutory architectures of all three jurisdictions. It evaluates them against key metrics of merit, transparency, political insulation, and diversity. A particular focus is placed on the often-overlooked distinction between appointment mechanisms for higher and lower judiciary, revealing a sharp dichotomy in Pakistan compared to more integrated approaches in the UK and the politicized uniformity in the US. The findings indicate that the 26th Amendment has not fully resolved the contentious nature of appointments in Pakistan. The study concludes by deriving lessons from the comparative analysis, suggesting that enhancing the role of an independent, merit-based commission, similar to the UK model, could strengthen the legitimacy and effectiveness of the Pakistani judiciary, offering concrete recommendations for future reform.